Comparative Study of Vitamin D Among Diabetic And Nondiabetic Chronic Kidney Disease Patients - Alam, Farzana; Barua, Prasun; Haque, Mahmudul; Uddin, AAM Ryhan; Din, Md Aftab E (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Chronic Kidney Disease (CKD) is a major health problem in Bangladesh. Diabetes mellitus is the most common cause of this pathology. Among individuals with CKD, vitamin D deficiency is very much prevalent. But there are not enough studies comparing vitamin D status of diabetic and nondiabetic CKD patients. So, this study aimed to compare the 25(OH)D levels between these two groups. Materials and methods: This cross-sectional comparative study was carried out in the Department of Biochemistry and the Department of Nephrology, Chittagong Medical College Hospital from June 2013 to May 2014. Fifty (50) diabetic CKD patients and fifty (50) age-sex matched nondiabetic CKD patients of 18-85 years fulfilling the required enrolment criteria were purposively selected to form two comparing groups. Patient-profiles were completed by history and physical examination. Anthropometric and clinical parameters were analysed along with fasting and 2 hours after breakfast plasma glucose, serum creatinine, eGFR, serum calcium, serum phosphate and 25(OH)D. Data were analysed by computer-based statistical software. The confidence level was fixed at 95% and p-value of <0.05 was considered significant. Results: In the study, all patients in both groups had hypovitaminosis D and the vitamin D deficiencies in diabetic and nondiabetic CKD patients were 100% and 84% respectively. Mean 25(OH)D was significantly lower in the diabetic group (5.48 ± 0.39 ng/mL) compared to nondiabetic one (9.08 ± 0.75 ng/mL), but the severity of vitamin D deficiency did not seem to correlate with CKD stages. Conclusion: In conclusion, this study establishes the high prevalence of vitamin D deficiency in both diabetic and nondiabetic CKD patients, but the deficiency was more severe in diabetic ones. JCMCTA 2019 ; 30 (2) : 16-21